2018
DOI: 10.1371/journal.pone.0204925
|View full text |Cite|
|
Sign up to set email alerts
|

Hatha yoga for acute, chronic and/or treatment-resistant mood and anxiety disorders: A systematic review and meta-analysis

Abstract: BackgroundThe aim of this study was to systematically investigate the effectiveness of hatha yoga in treating acute, chronic and/or treatment-resistant mood and anxiety disorders.MethodsMedline, Cochrane Library, Current Controlled Trials, Clinical Trials.gov, NHR Centre for Reviews and Dissemination, PsycINFO and CINAHL were searched through June 2018. Randomized controlled trials with patients with mood and anxiety disorders were included. Main outcomes were continuous measures of severity of mood and anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 95 publications
1
37
0
3
Order By: Relevance
“…20,28 Moreover, there are considerable differences in the forms of yoga employed, with many yoga publications not including the key components of yoga in the intervention. 29 This is an important limitation, given the distinct physiological and psychological impacts and outcomes noted among types of yoga practices. 30 As well, most RCTs did not employ comparators or assessed yoga against less rigorous control conditions (e.g., no treatment, wait-list).…”
Section: Yoga For Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,28 Moreover, there are considerable differences in the forms of yoga employed, with many yoga publications not including the key components of yoga in the intervention. 29 This is an important limitation, given the distinct physiological and psychological impacts and outcomes noted among types of yoga practices. 30 As well, most RCTs did not employ comparators or assessed yoga against less rigorous control conditions (e.g., no treatment, wait-list).…”
Section: Yoga For Depressionmentioning
confidence: 99%
“…Medication treatments for unipolar and bipolar depression have their own limitations, including adverse effects and poor adherence, 29 while psychological treatments are costly and often not accessible, thus increasing the risk of relapse and negative long-term outcomes. As such, new, effective, accessible, and patient-preferred treatment options would greatly enhance current treatments for depression.…”
Section: Rationale For This Studymentioning
confidence: 99%
“… 33 Another systematic review and meta-analysis done by Vollbehr et al showed variable dropout rate from 0% to 47% with a follow up dropout 14% to 67%. 51 In our study all the participants were apparently well which might have decreased the perceived benefit contributing for the dropout. In this study masking was not feasible as the lead author was the only person who collected all the data, including allocation group.…”
Section: Discussionmentioning
confidence: 60%
“…Apart from promotion of general health and well-being, yoga is advocated to ameliorate a variety of pathological conditions such as mood and anxiety disorders [2], where limited-to-moderate effects were found in symptom severity of depression and anxiety, comparable to medication and physical exercise interventions [3]. Nevertheless, based on a meta-analysis, no significant effects of yoga on symptoms of depression compared to treatment as usual were found [4].…”
Section: Introductionmentioning
confidence: 99%